Percutaneous transhepatic arterial access for coil embolization of hepatic artery infusion pump-associated bleeding - Anuj K. Dutta; Vishal Shankar; Ernesto G. Santos; Brett Marinelli; Erica S. Alexander; Vlasios S. Sotirchos; Ken Zhao (CVIR Endovascular)
Abstract Background Hepatic artery infusion pump (HAIP) chemotherapy is a locoregional treatment for intrahepatic malignancies. HAIPs are surgically implanted, and the catheter tip is typically inserted into a ligated gastroduodenal artery stump. Potential complications at the catheter insertion site include dehiscence, pseudoaneurysm or extravasation, and adjacent hepatic arterial stenosis and thrombosis. Bleeding complications can be treated with stent-graft placement or coil embolization across the injury site, typically with standard antegrade arterial approach into the hepatic arterial system by transfemoral or transradial access. However, in cases where an antegrade approach is not possible, alternative methods are necessary. Case presentation A patient presented with an enlarging hematoma due to bleeding at the gastroduodenal artery HAIP catheter insertion site. Emergent angiography revealed concomitant common hepatic artery occlusion and retrograde perfusion of the GDA via tortuous, diminutive hepatic collaterals which precluded standard antegrade approach. Collateral inflow from the dorsal pancreatic artery was utilized to opacify the right hepatic artery. The segment 5 hepatic artery was percutaneously accessed under fluoroscopic guidance, and microcoils were deployed both proximal and distal to origin of the gastroduodenal artery. The patient remained stable throughout the postoperative period and was discharged after an otherwise uneventful admission. Follow-up computed tomography demonstrated resolution of the hematoma and no bleeding or biliary complication from transhepatic access. Conclusions This report highlights the safety and efficacy of percutaneous transhepatic arterial access for endovascular management of HAIP associated bleeding at the gastroduodenal artery when standard antegrade interventions cannot be performed. Interventional radiologists caring for patients with HAIPs should be familiar with their potential complications and the range of techniques required for management.